Economic contributions of pharmaceutical interventions by pharmacists: a retrospective report in Japan. Issue 1 (December 2017) - Yasunaga, Daiki; Tasaka, Yuichi; Murakami, Satoshi; Tanaka, Akihiro; Tanaka, Mamoru; Araki, Hiroaki
Abstract Background Pharmacists in Japan currently play a key role in patient hospital care. Their responsibilities include filling prescriptions, checking a patient's medication history, and providing appropriate information to other health care workers. More importantly, pharmacists' interventions can also result in reductions in adverse drug reactions (ADRs) and, ultimately, in cost savings. This study aimed to determine the economic value of such interventions at a hospital in Japan. Methods At a single Japanese hospital, we analyzed 1452 pharmaceutical interventions by pharmacists, including recommending antibiotic dosage regimens, attending ward rounds with multidisciplinary health providers, providing drug information, and reporting ADRs. We classified the interventions into 13 categories. Using data from the PreAVOID Report by the Japanese Society of Hospital Pharmacists, along with previous studies, we estimated the cost savings of the interventions. Results Various savings could be realized through appropriate interventions by hospital pharmacists. Based on the amount paid by the Pharmaceuticals and Medical Devices Agency, we calculated the cost savings associated with preventing serious ADRs as 21, 400 USD ($) per case. The cost savings for recommendations related to transvenous antimicrobial therapy amounted to $1900 per patient. Pharmacists' interventions were able to prevent 12 cases of serious ADRs. Conclusions Determining the economic value of pharmacists' interventions is an important means of appraising the current role of hospital pharmacists. Our evaluation demonstrates the positive economic effects of pharmacists' interventions in a hospital setting.